Longterm catheterization of the lingual artery for intraarterial cytostatic therapy - Krajina, A; Hlava, A; Simůnek, A; Dimter, L; Hozová, E; Jirousek, Z; Steinhart, L (Sbornik vedeckych praci Lekarske fakulty Karlovy university v Hradci Kralove, 1991)
The authors present a technique of longterm lingual artery catheterization for intraarterial regional chemotherapy. The transtemporal approach enables safe introduction through the external carotid artery. Catheterization technique is presented in 16 patients with the diagnosis of carcinoma baseos oris and carcinoma linguae. Both the lingual arteries were infused in four patients with tumors spreading over the midline. The dislocation of the catheter was found seven times of twenty catheterizations. The following catheter repozition was always successful.
Keywords: Mouth Neoplasms; Infusions, Intra-Arterial; Tongue; intraarteriální infuze; protinádorové látky; Humans; Antineoplastic Agents; lidé; jazyk; nádory úst